2018
DOI: 10.5755/j01.ms.24.1.17319
|View full text |Cite
|
Sign up to set email alerts
|

Microindentation Hardness-Secondary Dendritic Spacings Correlation with Casting Thermal Parameters in an Al-9wt.%Si Alloy

Abstract: Experiments were carried out to analyze the effect of growth rates (VL) and cooling rates (TR) on both secondary dendritic arm spacings (λ2) and Vickers microhardness (HV) of an Al-9wt.%Si alloy during the horizontal directional solidification under transient heat flow conditions. A water-cooled solidification experimental apparatus was developed allowing a wide range of TR (from 0.2 to 3.5 ºC/s) to be experienced. Five computer guided thermocouples were connected with the metal, and the time-temperature data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
5
0
3
Order By: Relevance
“…In that figure, the dashed curves come from experimental functions that were fitted to the experimental data. As can be seen, in both cases λ 2 is affected by Ṫ, which is evidenced by the 34 and Carvalho et al 35 ) and show the effect of Ṫ on λ 2 . This effect translates to the microstructure growth, i.e., high values of Ṫ near the mold bottom favor a more refined microstructure, whereas low values of this thermal parameter close to the top of the castings contribute effectively to yield a coarser microstructure.…”
Section: Solidification Analysis Of Al -3 Wt % Si and Al -7 Wt % Si Alloysmentioning
confidence: 51%
“…In that figure, the dashed curves come from experimental functions that were fitted to the experimental data. As can be seen, in both cases λ 2 is affected by Ṫ, which is evidenced by the 34 and Carvalho et al 35 ) and show the effect of Ṫ on λ 2 . This effect translates to the microstructure growth, i.e., high values of Ṫ near the mold bottom favor a more refined microstructure, whereas low values of this thermal parameter close to the top of the castings contribute effectively to yield a coarser microstructure.…”
Section: Solidification Analysis Of Al -3 Wt % Si and Al -7 Wt % Si Alloysmentioning
confidence: 51%
“…Brito et al [53] (Al-3 wt%Mg alloy) and Spinelli et al [54] (hypoeutectic Al-Cu alloys, including the Al-3 wt%Cu alloy) have also proposed a -2/3 power law to represent the k 2 variation with G R for downward directionally solidified samples. Likewise, Costa et al [27] and Carvalho et al [55] have found exponential equations of the form k 2 = constant (C R ) -1/3 to correlate k 2 with C R for horizontally solidified Al-6 wt%Cu and Al-9 wt%Si alloys, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…, whose exponent (-2/3) has been validated by several experimental investigations on unsteady-state directional solidification of aluminum-based binary and multicomponent alloys, for both horizontal and vertical directions 2,16,17,23,[25][26][27][28]38,39 . Among the works on transient solidification, it is emphasized those reported for binary Al-Si 2,38,39 and multicomponent Al-Si-(Cu and Mg) 23,[25][26][27][28]30 alloys.…”
Section: Introductionmentioning
confidence: 82%
“…The dependence of the microhardness (HV) on the microstructure in Al-based binary and multicomponent alloys has been investigated for several directional solidification systems 23,28,38,[41][42][43][44][45][46][47][48] and the results obtained in these studies have shown that power and Hall-Petch types experimental equations may characterize the variation of HV with λ 1 , λ 2 and λ 3 , of which the alloys containing the Si as the major alloying element with Cu/Mg/Sn addition are highlighted. This can be seen in Table 1.…”
Section: Introductionmentioning
confidence: 99%